2011
DOI: 10.1111/j.1467-7687.2011.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Long trajectory for the development of sensitivity to global and biological motion

Abstract: We used a staircase procedure to test sensitivity to (1) global motion in random-dot kinematograms moving at 4° and 18° s(-1) and (2) biological motion. Thresholds were defined as (1) the minimum percentage of signal dots (i.e. the maximum percentage of noise dots) necessary for accurate discrimination of upward versus downward motion or (2) the maximum percentage of noise dots tolerated for accurate discrimination of biological from non-biological motion. Subjects were adults and children aged 6-8, 9-11, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 52 publications
7
103
3
Order By: Relevance
“…Finally, studies that also included adult observers produced mean adult thresholds of 20% coherence for preferential looking paradigms, 9,30,32 10% for OKR-based methods, 30,51 and 10% for behavioral responses. [34][35][36]64 However, as is evident from the variability in Figure 6, these comparisons should be interpreted with caution. In particular, the stimulus parameters and threshold criteria (i.e., whether thresholds reflect 50%, 63%, or 75% correct) differ across studies, which may lead to variations in absolute threshold (see Appendix for further details).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, studies that also included adult observers produced mean adult thresholds of 20% coherence for preferential looking paradigms, 9,30,32 10% for OKR-based methods, 30,51 and 10% for behavioral responses. [34][35][36]64 However, as is evident from the variability in Figure 6, these comparisons should be interpreted with caution. In particular, the stimulus parameters and threshold criteria (i.e., whether thresholds reflect 50%, 63%, or 75% correct) differ across studies, which may lead to variations in absolute threshold (see Appendix for further details).…”
Section: Discussionmentioning
confidence: 90%
“…9,10,[33][34][35][36] However, the development of global motion perception in early childhood is not well understood and currently no data are available for children between the ages of 7 months and 3.5 years. This may be due to the difficulties involved in measuring visual function in children of this age.…”
mentioning
confidence: 99%
“…23 For example, some studies reported that the global motion processing mechanisms follow a long and protracted developmental pattern extending beyond 14 years. [51][52][53] However, there are other studies reporting a similar maturation age for both global form and motion processing. 54,55 Recent studies question the generalizability of dorsal stream vulnerability in neurologic developmental disorders.…”
Section: Comparison Of the Global Motion And Form Deficits In Amblyopiamentioning
confidence: 86%
“…The behavioral restoration of both basic (2) and more complex visual functions (6)(7)(8), as well as multisensory processes (7,9,10), have been studied in this population. For example, face detection (2) and the processing of biological motion (11) have been found to be largely unaffected by periods of early visual deprivation lasting for a few months. By contrast, visual functions that rely on an automatic binding of visual features seem to be permanently impaired by short periods of visual deprivation, including configural face processing (6), the ability to recognize faces from different perspectives (7,12), and the detection of illusory contours (8).…”
mentioning
confidence: 99%